Separation of acteoside and linarin from Buddlejae Flos by high‐speed countercurrent chromatography and their anti‐inflammatory activities. Issue 8 (26th February 2020) - Xie, Guoyong; Yang, Jie; Wei, Xiaonan; Xu, Qiuhong; Qin, Minjian
Abstract: Buddleja officinalis Maxim., a deciduous, flowering shrub, is used as a traditional Chinese medicine; the bioactivity of B. officinalis is primarily due to flavonoids and phenylethanoid glycosides. In the study, acteoside and linarin were successfully isolated from B. officinalis by high‐speed countercurrent chromatography with a two‐phase solvent system composed of ethyl acetate: n ‐butanol: water (5:0.8:5, v/v/v). The purities of acteoside and linarin were determined to be 97.3 and 98.2%, respectively, using one‐step high‐speed countercurrent chromatography separation. The chemical structures of the two compounds were identified by electrospray ionization‐mass spectrometry and nuclear magnetic resonance. After separation, the anti‐inflammatory effects of the two compounds were evaluated using lipopolysaccharide‐induced human umbilical vein endothelial cells. Acteoside and linarin inhibited the expression of nitric oxide, tumor necrosis factor α and interleukin 1β, which demonstrated that acteoside and linarin possessed anti‐inflammatory activity.